Ex vivo modelling of oesophago-gastric cancer - Saunders, John (2017)
Introduction The response to neoadjuvant chemotherapy in oesophago-gastric (OG) cancer is only 40%, so over half of the patient’s disease will progress, whilst they also suffer the toxic chemotherapy side-effects. A model to predict chemotherapy response would provide a marked clinical benefit, by enabling personalised treatment of OG cancer.